1985
DOI: 10.1002/ana.410170310
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of neuropathological changes and dementia of Alzheimer's disease in Down's syndrome

Abstract: One hundred brains of patients with Down's syndrome (DS) who died in institutions for chronic care were examined for clinicopathological correlation of Alzheimer's disease. Fifty-one were below and 49 were above age 30 years at death. Tissues from the right, prefrontal, and hippocampal cortices were processed for microscopy using H&E and Bodian-periodic acid-Schiff impregnation. Morphometric evaluations of plaques and tangles were carried out. Plaques or plaques and tangles were found in the brains of 56 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
558
1
6

Year Published

1988
1988
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,069 publications
(572 citation statements)
references
References 20 publications
7
558
1
6
Order By: Relevance
“…Individuals with Down syndrome (DS) develop Alzheimer disease (AD) pathology in a progressive age-dependent manner [26,34,35,68] and as such, are at high risk for the development of dementia [29,33]. Clinical signs of dementia are more commonly observed when individuals are over 50 years of age [4,29,49,63].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with Down syndrome (DS) develop Alzheimer disease (AD) pathology in a progressive age-dependent manner [26,34,35,68] and as such, are at high risk for the development of dementia [29,33]. Clinical signs of dementia are more commonly observed when individuals are over 50 years of age [4,29,49,63].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical signs of dementia are more commonly observed when individuals are over 50 years of age [4,29,49,63]. By age 40 years, however, all individuals with DS have neuropathological changes including senile plaques and neurofibrillary tangles consistent with AD [35,67,68]. Senile plaques contain the β-amyloid peptide that is derived from a longer precursor protein, β-amyloid precursor protein (APP), the gene for which is on chromosome 21.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that a co-injection of fibrillar A␤ with excitatory amino acids into rat brains produced drastic and synergistic neuronal death, possibly due to an enhancement by A␤ of the susceptibility of neurons to excitatory amino acids in vivo (Morimoto et al, 1998). It remains unclear why A␤ deposition as diffuse plaques occurs 20 -30 years earlier than the neuronal degeneration in AD (Wisniewski et al, 1985;Mann et al, 1992), however, and why the hippocampal CA1 and the subiculum, both vulnerable areas in AD, exhibit little A␤ deposition, especially in the early stage (Braak and Braak, 1991). It is also unclear whether insoluble and deposited A␤ per se is directly responsible for the widespread neurodegeneration in AD ( Neve and Robakis, 1998;Chui et al, 1999).…”
mentioning
confidence: 97%
“…The aims of the study Early detection of Alzheimer's disease (AD), par ticularly in individuals at risk for developing AD [e.g., those with a family history of AD (Heston et al, 1981;St. George-Hyslop et al, 1987), or older individuals with Down syndrome (Burger and Vo gel, 1973;Wisniewski et al, 1985»), may be impor tant for possible treatment strategies. However, early diagnosis of AD has been difficult because of the quality of information available regarding ge-were to identify a discriminant function that would (a) distinguish patients from controls and (b) identify an AD pattern in an individual at risk for AD with isolated mem ory impairment whose initial PET scan showed minor abnormalities, but whose second scan showed parietal hypometabolism, coincident with further cognitive de cline.…”
mentioning
confidence: 99%